Analisis Hukum Pelaksanaan Ta'ziyah dan Talqin Mayit dalam Pandangan Mazhab Syafi'iyyah - Zulkifli Zulkifli (Journal Smart Law, 2022)
The implementation of ta'ziyah and talqin corpses is carried out when fard kifayah will be held at the funeral home, namely the number of people who come to pay their respects with the intention of paying homage. So that its implementation in the near future is limited to waiting for the completion of the fardhu kifayah implementation, namely bathing, shrouding, praying and burying the dead. The problem found is that the implementation of ta'ziyah is misinterpreted as an activity that is futile and has no benefits and is even considered as an act of heresy. Some people in Langkat Regency accept the implementation of ta'ziyah and talqin corpse because it is considered an act that was sunnahized by the Prophet Muhammad and followed by friends. The formulation of the problem in the research: How is the implementation of ta'ziyah and talqin corpse in the view of the Imam Shafi'i school? How is the legal analysis regarding the implementation of ta'ziyah and talqin dead according to the Imam Syafi'i school of thought? The results of this study are: The implementation of ta'ziyah and talqin mayit in the view of the Imam Syafi'i school that disaster experts and the Muslim community can hold ta'ziyah and provide food if the provision of food does not burden the disaster expert because the aim is to respect the pentakziah. The implementation of talqin corpses is intended for mortuaries and penta'ziyah congregations as reminders and advice. The implementation of ta'ziyah is different if it is categorized as a bid'ah practice and is unfounded. Instead, the decision regarding the implementation of ta'ziyah prioritizes social aspects. Regarding the issue of the permissibility of providing food in the implementation of ta'ziyah, originating from the mayyit expert is not a problem.